(untitled) (Ozone Therapy Global Journal, 2013)
The glaucoma is one of the main problems of health in ophthalmology. Objective: to characterize the therapeutic response of ozone therapy as integrative therapy compared to the conventional treatment. Methods: an observational, descriptive and prospectivestudy was performed in patients with Simple Chronic Glaucoma diagnosis using ozone, in the Service of Ophthalmology of the Military Hospital Carlos J. Finlay (Havana, Cuba), during the year 2009. The sample of 98 patients (196 eyes), receivedtherapy in order to improve the instability of the visual keenness and the intraocular pressure. Patients were assigned at random to two groups of 49 each one. Conventional treatment was applied to the first one; the other received conventional treatment plus ozone therapy, which consisted on the application of cycles of treatments(15 -20) for rectal route at intervals of six months. There were analyzed the variables age, gender, ethnicity, visual keenness, intraocular pressure and visual field. Results: the 60-year-old patients prevailed in the sample (51.02 %), the men (71.42 %) and not white skin (66.32%). Visual improvement and tensional control improvement was obtained in patients treated with ozone therapy (p=0.0146 and p=0.0352 respectively). Conclusions:Significant improvement (p< 0.05) was observed of the vision and of the intraocular pressure in the patients treated with conventional treatment integrated with ozone therapy. The visual field did not change in any studies groups